IDENTIFIKASI ALEL DAN KEKUATAN PEMBEDA EMPAT LOKUS DNA MIKROSATELIT KROMOSOM-Y PADA MASYARAKAT KLAN PANDE DI BALI UNTUK KEPENTINGAN FORENSIK - Junitha, I Ketut; Sara Wijana, I Made (Indonesian Journal of Legal and Forensic Sciences (IJLFS), 2018)
This research was conducted to know alleles variation and power of discrimination of four pair of primer: DYS19, DYS390, DYS393 and DYS395 of male Pande clan.  Epithelial cell mucus was collected  from  59 male of Gainer, Klungkung, Badung regencies and Denpasar city. Phenol chloroform method was used to extraction DNA from epithel cells sample.  Four primer pair was used to amplify DNA samples in PCR machine on 52-55oC annealing temperature. Amplicon  were running on PAGE 10% and visualized  with silver nitrate staining.  The DNA typing were conducted  to determinate of alleles size of amplicon  with plotting migration distance of amplicon on semi-log pepper.  Genetic diversity and power of discrimination was calculated used Microsoft Exell program.  The result of this research showed that 29 alleles were found range of 6-9 with mean 7.25 per locus. The genetic diversity is high category (0.739 ± 0.003, the highest diversity on DYS 390 locus  is 0.809 ±  0,004 followed by DYS395, DYS393 are 0,793 ±  0.004 and 0,720 ± 0.005 and the small one is 0.633 ±  0.003 on DYS19 locus. The power of discrimination (PD) of all loci are high category with average value is 0.892, because of / for this reason  all of loci usfulnes for  forensic purpose on pande clan in Bali.
Keywords: Pande clan, Alel type, microsatellite DNA, Y-chromosom, power of discrimination